2022
DOI: 10.1111/jam.15260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein on gut development, microbial compositions and mucin expressions in mice

Abstract: Aims: Dietary protein, as an important macronutrient, widely participates in host growth and metabolism. In this study, effects of different protein levels (14, 20 and 26%) on the gut development, microbial compositions and mucin expressions were studied in C57BL/6 mice. Methods and Results:The results showed that body weight and the relative weight of stomach and gut were decreased in low-protein diet-fed mice, whereas highprotein diet significantly reduced the villus length and area of jejunum. Goblet cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Consistent with many studies, diet can introduce different bacteria to the hosts (Anderson et al, 2012;Tang et al, 2012;Deb et al, 2019). In mammals, high-protein diet notably reduced microbial diversity and changed the microbial compositions at the phylum level (Li et al, 2022). In panda, butyrate-producing bacterium Clostridium butyricum was more abundant in gut during shoot-eating season than leaf-eating season (Huang et al, 2022).…”
Section: Diet Is the Main Source Of Microbiota In Predatory Mite Hostssupporting
confidence: 66%
See 1 more Smart Citation
“…Consistent with many studies, diet can introduce different bacteria to the hosts (Anderson et al, 2012;Tang et al, 2012;Deb et al, 2019). In mammals, high-protein diet notably reduced microbial diversity and changed the microbial compositions at the phylum level (Li et al, 2022). In panda, butyrate-producing bacterium Clostridium butyricum was more abundant in gut during shoot-eating season than leaf-eating season (Huang et al, 2022).…”
Section: Diet Is the Main Source Of Microbiota In Predatory Mite Hostssupporting
confidence: 66%
“…In mammals, high‐protein diet notably reduced microbial diversity and changed the microbial compositions at the phylum level (Li et al. , 2022). In panda, butyrate‐producing bacterium Clostridium butyricum was more abundant in gut during shoot‐eating season than leaf‐eating season (Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The LPS levels in the H-RES-HMB group were lower than those in the other three groups, resulting in a decrease in the abundance of Proteobacteria in this group. It has been reported that highprotein diets alter the abundance of Proteobacteria [56]. Current studies have shown that Proteobacteria are involved in metabolic disorders and inflammatory bowel disease [57], while RES and HMB supplements have anti-inflammatory and anti-cancer properties that may contribute to the reduced abundance of the Proteobacteria microflora [44].…”
Section: Discussionmentioning
confidence: 99%